Eletrodos impressos descartáveis: aplicações em amostras ambientais, alimentícias e combustíveis - Squissato, André Luiz (2019)
This thesis presents the potential association between electroanalytical techniques (voltammetric and amperometric) and disposable printed electrodes for the development of fast and portable methods in the monitoring and/or quality control of environmental, food and biofuels samples. The first part of the thesis presents the use of a organic resistant screem-printed graphite electrode (SPGrE) coupled to the batch injection analysis system (BIA) with amperometric detection for continuous monitoring of the inhibitor of corrosion, 2,5 dimercapto-1,3,5-thiadiazole (DMCT), in fuel ethanol, synthetic sea water and mineral oil. Samples were diluted in hydroethanolic electrolyte (95% v/v ethanol containing 0.1 mol L-1 of H2SO4). The analytical system can be used continuously for more than 200 consecutive injections (100 μL sample volume at 193 μL s-1) free of DMCT adsorption effects, with rapid responses (180 h-1) and precise (RSD < 3% n = 10) and limit of detection (LOD) of 0.3 µmol L-1. Accuracy was assessed by addition and recovery tests (93-106%) and comparison with spectrophotometric method. The second part of the thesis consists of the use of screen-printed gold electrodes (SPGE) associated to the Square Wave Anodic Stripping Voltammetry (SWASV) for the determination of mercury in fish-capsule oil-based supplements. Three procedures of preparation of the oily samples were evaluated: calcination, ultrasonic assisted digestion and digestion block. The ultrasonic bath was more efficient in the extraction of mercury from the oil presence of a concentrated mixture 1:1 (v/v) HCl/H2O2 at room temperature. Fifteen minutes of exposure to the ultrasonic energy were sufficient for the extraction of the metal into aliquots of 100 mg of a certified oil standard containing mercury. The LOD was estimated to be 0.25 mg L-1 and a linear range between 5 and 400 mg L-1 was obtained with 90 s of deposition time in the support electrolyte composed of a 0.1 mol L-1 solution of HCl. The fish oil samples analyzed showed Hg(II) concentration below the LOD value. The recovery values for samples spiked with the Hg-containing oil standard ranged from 95 to 105%. The method was accurate (DPR < 3.8%, n = 10) and the electrodes were continuously used (about 100 analyzes without substitution) under the presence of the dilute oxidant mixture. The third part of the thesis involves the use of SPGE resistant to organic solvents to develop a sensitive and rapid method in the direct determination of free copper in biodiesel and to correlate the results with the oxidative stability of the biofuel. Immersion tests of copper plates in biodiesel for different periods provided the contamination of the fuel with copper due to the corrosive characteristics of biodiesel. The SWASV technique allowed the determination of Cu(II) ions in the biodiesel after a simple dilution of the samples in 90% (v/v) ethanol containing 0.1 mol L-1 of HCl (supporting electrolyte). The stability to the oxidation of biodiesel based on the values of the induction period (IP) was performed by the Rancimat method. The results indicated a direct correlation between the reduction of the oxidative stability of biodiesel and the free copper content instead of the total biodiesel content. SPGEs responded 80 consecutive measurements before replacement by a new electrode. The method is considered repetitive (RSD <5% for n = 10), free of matrix interference (recovery between 99 and 105%) and LOD of 1.5 μg L-1 (corresponding to 1.7 μg kg-1). All methods developed allowed rapid, accurate and accurate analysis of complex samples with low reagent consumption and low effluent generation, as well as the potential for field analysis